2008
DOI: 10.1136/gut.2008.155481
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble CO-releasing molecules reduce the development of postoperative ileus via modulation of MAPK/HO-1 signalling and reduction of oxidative stress

Abstract: Pre-treatment with CO-RMs markedly reduced IM-induced intestinal muscularis inflammation. These protective effects are, at least in part, mediated through induction of HO-1, in a p38-dependent manner, as well as reduction of ERK1/2 activation. In addition, CORM-induced HO-1 induction reduces the early "oxidative burst" in the mucosa following IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 56 publications
(63 reference statements)
7
108
0
1
Order By: Relevance
“…In other in vitro and in vivo investigations involving either mice or rats [24][25][26][27], COHb concentrations varied following CORM exposure, with little increase seen with CORMs that release CO quickly (e.g., CORM-3, tricarbonyldichloro(glycinato)ruthenium (II)), contrasted with COHb values between 8% to 17% after exposure to slow releasing CORMs (e.g., CORM-A1, sodium boranocarbonate, Na 2 [H 3 BCO 2 ]). In sum, when exposed to CO at low or high concentrations (based on COHb), platelet function and measures of intravascular thrombus formation were decreased in mice and rats [18][19][20][21][22][23].…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Anmentioning
confidence: 99%
“…In other in vitro and in vivo investigations involving either mice or rats [24][25][26][27], COHb concentrations varied following CORM exposure, with little increase seen with CORMs that release CO quickly (e.g., CORM-3, tricarbonyldichloro(glycinato)ruthenium (II)), contrasted with COHb values between 8% to 17% after exposure to slow releasing CORMs (e.g., CORM-A1, sodium boranocarbonate, Na 2 [H 3 BCO 2 ]). In sum, when exposed to CO at low or high concentrations (based on COHb), platelet function and measures of intravascular thrombus formation were decreased in mice and rats [18][19][20][21][22][23].…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Anmentioning
confidence: 99%
“…The water soluble CO-RMs (CORM-3 and CORM-A1) [20,21] have gained increasing interest recently due to their promising pharmacological properties as carriers of therapeutic doses of CO in models of disease including gastrointestinal disorders [22,23]. Indeed, in a murine model of postoperative ileus, we have shown that the "fast" CO releaser CORM-3 markedly reduced 6 the manipulation-induced inflammation of the muscularis and improved surgically induced intestinal dysmotility. This was accompanied by reduction of the early oxidative burst in the mucosa [6].…”
Section: Introductionmentioning
confidence: 88%
“…Notably, in a mouse model of postoperative ileus we recently reported an early and transient increase in oxidative stress in the mucosal layer, with a peak value at 1 h after intestinal manipulation, preceding the peak in the muscularis [6]. The combination of oxidative stressinduced epithelial cell damage, increased intestinal permeability and translocation of intraluminal endotoxins might trigger the muscular inflammation [7]; TNF-α may play a role 5 in this epithelial distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the iron may be utilised in haemoglobin synthesis as evident in HMOX1 deficient mice that developed iron deficiency anaemia as a result of low serum iron levels (Poss and Tonegawa 1997;Yachie et al 1999). On the other hand, CO has recently been acknowledged as a second messenger of the anti-inflammation signalling transduction pathways in various tissues that can consequently promote overall anti-apoptotic effect (Maines 1997;Brouard et al, 2002;Micheau and Tschopp, 2003;Arruda et al, 2004;Wegiel et al, 2008;De Backer et al, 2009;Gozzelino et al, 2010).…”
Section: Excretion Glucuronidesmentioning
confidence: 99%